2019
DOI: 10.1177/0003489418802284
|View full text |Cite
|
Sign up to set email alerts
|

Glottic Stenosis: An Anatomic Analysis and New Treatment With a Self-Retaining Interarytenoid Spring

Abstract: Introduction: Endotracheal (ET) intubation is a common cause of acquired glottic stenosis. Severe cases often require an irreversible arytenoidectomy/cordectomy, which typically results in poor voice quality. Adult human cadaver larynges were studied to gain insights about ET tube–induced posterior glottic injuries, hoping to create a less invasive remedy. Study Design: Human cadaver investigation and case reports. Methods: Microlaryngeal assessments were done on 10 human cadaver larynges (5 men, 5 women) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…3 PGS type I is the rarest type and is frequently caused by intubation injury to interarytnoide tissue that causes pressure necrosis, mucosal breakdown, formation of granulation tissue, and subsequent scarring. 1,7 Laryngotracheal trauma during intubation should be minimized in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 PGS type I is the rarest type and is frequently caused by intubation injury to interarytnoide tissue that causes pressure necrosis, mucosal breakdown, formation of granulation tissue, and subsequent scarring. 1,7 Laryngotracheal trauma during intubation should be minimized in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Type I posterior glottic stenosis (PGS) is most prevalent as a result of prolonged endotracheal (ET) intubation. 1 The main reasons to post-intubation stenosis are: intubation trauma and injuries caused by ET tube pressure. Due to oro-pharyngeal curvature the ET tube, at all times, lies in the posterior glottis.…”
Section: Introductionmentioning
confidence: 99%
“…He was reconstructed with a large aortic homograft, and a modified T-tube stent. 11 He is decannulated (B,D) and has an excellent supraglottic sound source similar to a patient who undergoes a supracricoid partial laryngectomy. Note that the right arytenoid cartilage is affixed to the thyroid lamina (B).…”
Section: Discussionmentioning
confidence: 99%
“…(A,C) He underwent an extensive transmural right‐sided transcervical tumor removal along with a portion of the inner table tumor of the left. He was reconstructed with a large aortic homograft, and a modified T‐tube stent 11 . He is decannulated (B,D) and has an excellent supraglottic sound source similar to a patient who undergoes a supracricoid partial laryngectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Steven M. et al [16] reported that intubation is the most commonly observed etiology of acquired laryngeal stenosis at present, and for inhalational thermal injury, Allison Reid et al [17] suggested that it is di cult to distinguish laryngeal stenosis that arise from intubation or inhalational injury. The study conducted by Bruce Benjamin et al [18] revealed that granuloma on the vocal process of the posterior glottis, which proceeds from granulation tissues, is one of the main sequelae of intubation.…”
Section: Granulation Tissue In Glottis Observed Under An Endoscopementioning
confidence: 99%